Prevalence and risk factors associated with asthma in adults: a multi-country survey - Tsodzai, Rufaro Blessings (Department of Public Health and Family Medicine, 2025)
Background: The Global Asthma Network conducted a parent study that gathered data at the population level on children in two specific age groups, as well as on the adult caregivers of those children. The scope of this dissertation will be specifically narrowed down to examining the prevalence of asthma and related risk factors among adult caregivers. The analysis will primarily focus on determining the strength of association between known risk factors that can cause or trigger asthma symptoms in adults. Additionally, the study aims to explore how these identified risk factors may vary across different WHO regions and individual countries. Methods: Part A of this mini thesis presents the study protocol which outlines the literature review, rationale, aim and objectives of the study; the research methodology, analysis plan and ethical considerations. Part B is the journal-formatted manuscript which presents the results and discussion of the study findings in relation to other authors. Vancouver referencing style was used for this mini dissertation as required by the European Respiratory Journal (ERJ). Part C is the appendix section which presents some figures not included in the main paper, ethical approval, and instruction for authors. This study utilizes individual-level data collected from the Global Asthma Network (GAN). The parent study was a large observational cross-sectional, multi-country and multi-center epidemiological study. This study was conducted in several countries around the world. Countries ranging from low, middle, and high income were included in the study with the intention being to obtain data on different risk factors associated with asthma. The study surveyed two age groups of children (13/14 and 6/7) years and adult caregivers of both age groups. Data were obtained from centers located in the different geographical areas within each country, centers participating in the study were recommended to follow a protocol prescribed by the Global Asthma Network Steering Group (GANSG). Results: Among nineteen countries that took part in this study, 194,571 adults responded to the questionnaire related to asthma, eczema, and hay fever related symptoms. Out of 194,571 individuals, 89,315 (45.9%) were male and 105,256 (54.1%) were female. Countries which had highest participation rate was India and Mexico. Among adults that ever-had asthma, the highest proportion was from the Western Pacific region (8.8%), followed by Eastern Mediterranean region (8.5%), America (6.0%) and Europe (5.1%), while the lowest proportion was from South East Asia with (2.2%) and Africa (3.0%). From 12940 adults who reported to have current asthma symptoms (experienced wheezing in the last 12 months), the region with highest prevalence was Eastern Mediterranean (10.7%), followed by America (9.7%), Europe (8.3%) and Western Pacific (8.2%) region whereas lowest prevalence of current asthma symptoms was in South East Asia (3.6%) region. The analysis showed odds ratio for adult caregivers reported to reside in damp household was [1.64 (95% CI: 1.55 - 1.73)] for current wheeze, and [1.74 (95% CI: 1.61 - 1.89)] for severe asthma symptoms while exposure to moulds the OR was [1.35 (95% CI: 1.27 - 1.43)] for current wheeze, and [1.49 (95% CI: 1.37 - 1.63)] for severe asthma symptoms. The OR for biomass and solids as cooking fuel was 1.64 (95% CI: 1.43 – 1.88) and 1.19 (95% CI: 0.97 – 1.46) for severe asthma symptoms. Smoking OR for adult caregivers who self-reported as active adult smokers was 1.16 times as likely to report asthma symptoms. vi Conclusion: The study observes high prevalence in the estimates and symptoms of asthma between the six WHO regions and nineteen countries that were part of the study sample. Associated risk factors for asthma varied across the WHO regions and significant relationship with high risk of reporting current and severe asthma symptoms were observed.